Antimicrobial activity, In silico analysis, and molecular docking studies of an iodide-bridged dimeric palladium complex: a comprehensive insight - Nur Anis Nabilah Mohd Fuzi,; Khairil Anuar Jantan,; Amirul Ridzuan Abu Bakar,; Nik Muhammad Azhar Nik Daud,; Mohammad Noor Jalil,; Hamizah Mohd Zaki,; Jamil Mohamed Sapari,; Shamsul Bahrin Gulam Ali, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The iodide-bridged dimeric palladium complex [NnBu4]2[Pd2I6] was synthesized and characterized using various physiochemical analyses, including elemental and thermal analysis, UV-Vis, FTIR, and NMR spectroscopy. The antibacterial activity of the compound was evaluated using the disk diffusion method against a panel of bacteria, demonstrating broad-spectrum effectiveness against two Gram-positive bacteria (Bacillus cereus & Bacillus subtilis) and four Gram-negative bacteria (Salmonella typhimurium, Escherichia coli, Klebsiella aerogenes & Klebsiella pneumoniae). Molecular docking studies revealed a calculated binding energy score of -9.90 kcal/mol against the Thymidylate Kinase (TMK) protein, suggesting potential interaction and affinity. Physicochemical parameters, as the Swiss ADME web server predicted, indicated limited permeability across the blood-brain barrier and no gastrointestinal absorption. The Lipinski and Egan models predicted favorable drug-like characteristics for [NnBu4]2[Pd2I6]. [NnBu4]2[Pd2I6] was classified as Toxicity Class 3 for acute oral toxicity, with an LD50 value of 189 mg/kg. Predictive modeling using the ProTox-III web server yielded an average similarity of 88% and prediction accuracy of 71%. In conclusion, the obtained biological data suggest that [NnBu4]2[Pd2I6] could be a promising candidate for future development as an antibacterial agent.